ANALISIS KELAYAKAN FINANSIAL USAHA PEMBIBITAN KELAPA SAWIT (Elaies guineensis jacq) PADA CV.REMBAKA AGRI DI KABUPATEN BENGKULU UTARA - Ardi Setiyanto; Rita Feni; Jon Yawahar; Maheran Mulyadi; Edi Marwan (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2023)
This is study to determine the finansial feasibility and sensitivity value of the oil palm nursery business at CV. Rembaka Agri, Bukit Makmur Village, Pinang Raya District, Bengkulu Utara Regency. The method used in this research is the csa study method. A case study is a detailed examination of one setting, one object, one document repository, or one particular event. The respondent in this research is one respondent. This research was carriet out from November to desember 2022 at CV. Rembaka Agri in Bukit Makmur Village, Piang Raya District, Bengkulu Utara Regency is profitable. Under circumstances positive NPV of Rp 150.189.792. Net B/C = 1,12 and Internal rate of return = 22,60%. In the analysis of the sensitivity of cost solar up 5% positif NPV of Rp 151.701.207, Net B/C = 1,12 it means >1 and Internal rate of return = 22,68% then the business is worth pursuing. If in a state of rising seed prices 5% NPV positif Rp 345.562.679, Net B/C = 1,31 and Internal rate of return = 34,46%. Keywords : Financial feacibility of Oil Palm Nurser